The Effects of Advertisement and Brand Beliefs Towards Brand Attitude: The Case of the Mobile Phone Industry - Alwie, Aryaty (2001)
Today, telecommunication plays an important role in our daily activity. Mobile phone as one component in the telecommunication industry also plays its role to connect people in this global edge. Thus, it is not surprising when many telecommunication providers advertise their services using television, radio or other communication tools in order to attract their potential customers. The question arises in our mind on to what extent does the ads achieve their objective, which is to pursue people to subscribe to their services. The purpose of the study was to investigate the effects of attitude toward the ad and brand beliefs toward the attitude to the brand. Previous studies found that when a person holds a positive attitude toward an ad for a particular brand and hold a positive brand belief, this person will hold a favorable attitude toward the brand. This study tries to apply this model in local perspectives, among the younger generations. The study uses four mobile phone network brands from six brands available currently. These brands are Celcom, Maxis, lMTouch and DiGi nus study uses Faculty of Economics and Management's students as respondents. These students were assembled in one classroom and they were asked to see the selected advertisements before they were allowed to answer the questionnaire attached to them. The findings from the study showed that the respondents are having a favorable attitude toward the ads advertised by mobile phone network operators and positive belief toward these brands, where it lead to a positive attitude toward the brand or brand attitude. A regression analysis shows that these three variables are having a Significant relationship for all four brands in study as proposed by the previous model. However, to get a better understanding for this study, further study can be done focusing on these three variables but in more control situation, such as using a similar advertisement concept.